63. Guillain-Barrè syndrome with marked pleocytosis in the cerebrospinal fluid: A case report. Issue 12 (December 2017) - Stipa, G.; Carletti, S.; Frondizi, D.; Fanelli, C.; Gobbi, D.; Mancini, A.; Moschini, E.; Caproni, S.; Di Schino, C.; Galletti, F.; Colosimo, C.
Abstract : A 71 years old female patient referred to her Physician for left hip and abdominal, nigh-time worsening pain. For this reason, she underwent a lumbosacral vertebral MRI, that highlighted the presence of L3-S1 left radiculopathy. After two weeks, she developed a left VI and VII cranial (peripheral) nerves palsy. Admitted to hospital, she underwent brain CT and MRI, that resulted unremarkable. In Neurology division, on examination a left VI cranial nerve palsy, a bilateral VII cranial nerve palsy, dysarthria, dysphagia and increased tendon reflexes were observed. The neurophysiology investigation revealed diffuse delayed F-waves with axonal response, absent H reflex, asymmetrical skin reflex, normal distal M-waves latencies, central and peripheral motor and sensitive conduction, and EEG. In light of these findings, matching the hypothesis of acute polyradiculoneuritis a lumbar puncture was performed. Increased CSF proteins and white cell count were found, while microbiological exams were unremarkable. A combination iv treatment (ceftriaxon, acyclovir, human IG) was established. Because of the onset of tetraparesis and respiratory failure, the patient was admitted to the intensive care unit. Even if case of CSF pleocytosis (>50/ μ l) a differential diagnosis should be considered 1–2 this case report suggests that Guillain-Barrè diagnosis can not defectively ruled out.